2016
DOI: 10.1007/s11046-016-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Effects of a Polymeric Biosurfactant in Candida krusei and Candida albicans Cells

Abstract: This study evaluated the effects of a polymeric biosurfactant produced by Trichosporon montevideense CLOA72 in the adhesion of Candida albicans and Candida krusei cells to human buccal epithelial cells and its interference in biofilm formation by these strains. The biofilm inhibition by biosurfactant (25 mg/mL) in C. krusei and C. albicans in polystyrene was reduced up to 79.5 and 85 %, respectively. In addition, the zeta potential and hydrodynamic diameter of the yeasts altered as a function of the biosurfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In this way, BS could induce changes in the cell surface characteristics and modify the interface contributing to the inhibition of the adherence of yeast to the epithelial cells. In addition, the cell surface differences in carbohydrate and protein concentrations between the Candida strains could contribute to the modulation of cell adhesion [57].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, BS could induce changes in the cell surface characteristics and modify the interface contributing to the inhibition of the adherence of yeast to the epithelial cells. In addition, the cell surface differences in carbohydrate and protein concentrations between the Candida strains could contribute to the modulation of cell adhesion [57].…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the antimicrobial activity were associated with alkyl chain elongation [22]. The supposed interpretation of the SCGS antibacterial activity was attributed to an electrostatic interaction between the positive ammonium group, R 4 N + of the SCGS, and the negatively charged lipoprotein of the bacterial cell membrane, which leads to cell disruption [23]. In addition, the hydrophobic chain of the SCGS easily penetrated the microbial cell membrane, which led to damage of the cell's selective permeability and, consequently, the death of the cells [10].…”
Section: Staphylococcusmentioning
confidence: 99%
“…Much research has reported the antimicrobial activity of synthesized cationic surfactants that have 10 or 12 carbon atoms in their alkyl chain (Liu et al, 2015;Murguía et al, 2008;Obłąk et al, 2013). The supposed interpretation of the synthesized Gemini cationic surfactants' antibacterial susceptibility was attributed to an electrostatic interaction between the positive ammonium group, R 4 N + of the synthesized compounds, and the negatively charged lipoprotein of the bacterial cell membrane, which leads to cell disruption (Ferreira et al, 2016). In addition, the hydrophobic chain of the synthesized Gemini cationic surfactants can easily penetrate the bacterial cell membrane, leading to damage of its selective permeability and, consequently, death of the cells (Cornellas et al, 2011).…”
Section: Application Of the Synthesized Fhpao Fhpad And Fhpah Geminmentioning
confidence: 99%